Análise comparativa de metodologias para cálculos em efeito solo, empregando três configurações alares retangulares - Rogerio de Assis Dias Guahy (2019)
This work presents the comparative analysis of two methodologies for the calculation of aerodynamic parameters in the ground effect, applied in three rectangular wing configurations, in order to identify the most suitable methodology to be employed in a preliminary ground wing vehicle design and to verify the possibility of using an analytical method in the range of flight height and speed studied, in view of the ease of implementation of their formulations. The main concepts involved in the aerodynamics of subsonic aircraft are initially presented in order to make a bibliographic review of the principles of diverse nature that guide the operation of these vehicles both in the free atmosphere and in the ground effect, whose related concepts are also commented in a specific item of this work. The wing surfaces analyzed can be used in a winged vehicle with a ground effect that will operate at very low height and at a subsonic speed. Among the analytical methods investigated when reading several articles on the subject, the combined asymptotic expansion method proposed in 1969 by two US researchers was selected for the analytical determination of the aerodynamic parameters, evaluation and analysis of the three wing configurations. studied three-dimensional rectangular blocks, in view of the simplicity of their formulations, which makes it a suitable candidate for use in the conceptual and preliminary phase of the aeronautical design of winged vehicles with ground effect. As for the numerical method chosen for comparison, we opted for the ground surface wing support method proposed in 2011 by two Chinese researchers, which, although presenting greater complexity of implementation, as it requires the elaboration of a computer program, is more accurate. in the various speed ranges and flight heights studied. The results were analyzed, discussed, and presented in the item dedicated to the analysis of results, where it can be seen that the numerical method actually has some advantages over the analytical method, producing greater precision, although the analytical method allows a faster resolution, without the need for more elaborate and complex computational resources.